ESP Teachers’ Professional Development during the Time of Crisis: A Blessing in Disguise - Iswati, Luluk; Dwi Setyo Hastuti, Saptin (Universitas Sarjanawiyata Tamansiswa, 2023)
Teacher professional development is considered vital to the continuation of teaching improvement so that students' learning outcomes can be optimally achieved. The Covid-19 pandemic that struck the world had tremendously changed not only the teaching and learning process but also increased the opportunities for teacher professional development. Webinars, virtual conferences, and workshops are flourishing so teachers can easily access them with little effort. Despite the joy that the pandemic had brought toward teacher professional development, investigating to what extent the professional development programs have enhanced teachers' development was essential. Hence, this study explored to what extent the professional development activities increased areas of professional development according to Richards & Farrel (2005) i.e., subject-matter knowledge, pedagogical expertise, self-awareness, understanding of learners, understanding of curriculum and materials, and career advancement during the time of crisis. Data were gathered through interviews with six ESP teachers in Yogyakarta higher education institutions. The findings implied the need of teachers' self-evaluation on their professional development activities, especially areas of professional development that were still lacking and needed to be enhanced.